2019
DOI: 10.1159/000503036
|View full text |Cite
|
Sign up to set email alerts
|

The Outcomes of Switching from Short- to Long-Term Intravitreal Corticosteroid Implant Therapy in Patients with Diabetic Macular Edema

Abstract: <b><i>Background:</i></b> First-line treatment for diabetic macular edema (DME) is usually with antivascular endothelial growth factor agents, followed by intravitreal corticosteroids as a second-line treatment option. Long-term corticosteroids may offer quality of life and effectiveness benefits over short-term implants. <b><i>Objectives:</i></b> To evaluate outcomes of patients with persistent or recurrent DME who switched from a short-term (dexamethasone) to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Studies that evaluated the functional efficacy of the FAc implant ( n = 22 studies) had a mean follow-up of 20.0 months (range: 8.5–36.0 months, median: 18.0 months) [ 15 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Mean baseline BCVA was 50.8 letters (range: 45.7–71.0 letters, median: 51.6 letters) and improved to a maximum of 59.5 letters (range: 49.0–74.8 letters, median: 57.2 letters) after FAc implant injection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that evaluated the functional efficacy of the FAc implant ( n = 22 studies) had a mean follow-up of 20.0 months (range: 8.5–36.0 months, median: 18.0 months) [ 15 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Mean baseline BCVA was 50.8 letters (range: 45.7–71.0 letters, median: 51.6 letters) and improved to a maximum of 59.5 letters (range: 49.0–74.8 letters, median: 57.2 letters) after FAc implant injection.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 22 studies retained, only those assessing both functional and anatomical efficacy were used for this analysis ( n = 18 studies) [ 26 , 27 , 28 , 29 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Functional efficacy was defined as a BCVA improvement of at least five letters, while anatomical efficacy as a CRT decrease by 20% or more ( Figure 4 ) similarly to the definitions used by the DRCRnet study group [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the literature on alternative corticosteroids is still sparse, some studies have shown that triamcinolone acetonide intravitreal injections result in similar rates of ocular hypertension compared to dexamethasone implant 104,105 . Similarly Vaz-Pereira et al could not find a significant difference in IOP after switching from dexamethasone to fluocinolone acetonide 106 . More research will have to be done in order to be able to more clearly distinguish the pros and cons of the different corticosteroid injections available.…”
Section: Summary Of Findingsmentioning
confidence: 87%
“…38 It has also been previously stated that the FAc implant could be an alternative option for those DME patients that showed insufficient response to either anti-VEGF agents or short-lasting corticosteroids. 80,81 Owing to the insufficient response to previous treatments in Phase IV studies, the FAc implant could also be an option for patients that do not have a complete anatomical response or vision improvement after one injection of dexamethasone implant, as has been demonstrated in real-world practices, 82 because the FAc implant contains a different molecule that could induce a different response.…”
Section: Recommendation -Patients That May Benefit From Fac Implant Tmentioning
confidence: 99%